1991
DOI: 10.1152/ajpheart.1991.260.3.h985
|View full text |Cite
|
Sign up to set email alerts
|

SA nodal parasympathectomy delineates autonomic control of heart rate power spectrum

Abstract: The purpose of this study was to quantify the relative roles of the canine cardiac parasympathetic and sympathetic nerves in controlling the distribution of power within the heart rate (HR) power spectrum using a highly selective surgical technique to parasympathectomize the SA node. DAta were recorded in awake dogs (n = 6) before and after the selective denervation; the animals were isolated from human contact and their behavior carefully monitored during the measurements. The average amplitude in the high-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
0
3

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(100 citation statements)
references
References 0 publications
4
93
0
3
Order By: Relevance
“…8,16 The low-to high-frequency ratio therefore reflects the balance between the sympathetic and the parasympathetic activities. [30][31][32] Studies from Siira et al and Salamalekis et al showed a predominant increase in the low-frequency domain and, therefore, a higher low-to high-frequency ratio in acidotic fetuses, consistent with the increase in sympathetic system activity induced by hypoxia. 16,19,31,32 Interestingly, one of the multifractal parameter we studied (zeta(2)), which is related to low-to highfrequency ratio, also showed a predominant increase in sympathetic component when fetal acidosis developed.…”
Section: Discussionmentioning
confidence: 70%
“…8,16 The low-to high-frequency ratio therefore reflects the balance between the sympathetic and the parasympathetic activities. [30][31][32] Studies from Siira et al and Salamalekis et al showed a predominant increase in the low-frequency domain and, therefore, a higher low-to high-frequency ratio in acidotic fetuses, consistent with the increase in sympathetic system activity induced by hypoxia. 16,19,31,32 Interestingly, one of the multifractal parameter we studied (zeta(2)), which is related to low-to highfrequency ratio, also showed a predominant increase in sympathetic component when fetal acidosis developed.…”
Section: Discussionmentioning
confidence: 70%
“…to cardiac variability (18)(19)(20). Automated analyses of and heart rate variability have been described in healthy digitally acquired cardiorespiratory signals can also help full-term newborns (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…27,29,30 Although many investigators use the LF band as an index of sympathetic modulation, this practice is somewhat controversial because of the additional contribution of parasympathetic tone. 25 VLF power (0.003-0.04 Hz) represents the sympathetic activity.…”
Section: -28mentioning
confidence: 99%